THE IMPORTANCE OF USING MODERN PEDAGOGICAL TECHNOLOGIES IN PHYSICAL EDUCATION LESSONS: Kazakov. Sodiq Ramazonovich - is an associate professor of the Department of Rehabilitation, Special Medicine and Physical Education of the Bukhara State Medical Institute., Kazakov. Sodiq Ramazonovich (Лучшие интеллектуальные исследования, 2024)
The article discusses the importance of the use of modern pedagogical technologies in physical education and sports lessons, some recommendations on the formation of worldview and thinking, the formation of physical, spiritual and moral qualities.